Application of a γRS index-based method and techno-economic analysis for in situ treatment of 137Cs-contaminated soils by cement-barite based stabilisation/solidification. (15th July 2017) - Falciglia, Pietro P.; Romano, Stefano; Vagliasindi, Federico G.A.
Abstract: This paper examines the application of cement (C)-barite (Ba) based-Stabilisation/Solidification (S/S) for the remediation of 137 Cs-contaminated soils, investigating the influence of soil: grout and C: Ba ratios on the shielding performance of the S/S mix assessed as gamma radiation shielding ( γRS ) index variation. Results from experiments were used to perform a novel approach and an economic analysis in order to calculate the effective dose reduction achievable by S/S and to assess the optimum quantities and costs of selected mixes, respectively. Gamma ray spectrometer measurements indicate that γRS index increases with increasing barite percentage up to a maximum level of 50%; however a further increase results in a worsening of the shielding performances. A maximum γRS variation of 46.5% was recorded with grout percentage increasing from 16.6 to 50%. At the photon energy of 662 keV ( 137 Cs), the maximum grout amount results in the possibility to shield up to 24.1% of γ-rays emitted. The effective dose reduction achievable by the investigated S/S allows a maximum 137 Cs-soil contamination in the range 2.94–14.55 kBq kg −1 successfully treatable employing a soil: grout ratio of 1: 1 (C: Ba = 1:1). Technical data, jointly with economic analysis findings, make cement-barite based-S/S very competitive in cost-effectiveness and could provide a basis for decision-making of 137 Cs-contaminated site remediation. Highlights: We investigate the influence of soil: cement: barite ratios on the γRS index variation. We elaborate γRS index-based calculations to assess the effective dose variation achievable by S/S. We assess optimum quantities and specific costs for the S/S of 137 Cs-contaminated soils. γRS is strictly linked to the S/S mix density and it increases with increasing barite percentage. Experimental findings and techno-economic analysis are useful for real-scale S/S activity planning.